2012
DOI: 10.1111/j.1365-2265.2012.04385.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant lithium improves the efficacy of radioactive iodine treatment in Graves' and toxic nodular disease

Abstract: SummaryContext Lithium increases iodine retention in the thyroid gland and inhibits thyroid hormone release. Although lithium has been reported to improve the efficacy of radioactive iodine (RAI) treatment in Graves' disease, its role as an adjunct to RAI treatment of hyperthyroidism, particularly in toxic nodular disease, remains contentious. Objective To assess whether adjuvant lithium increases the efficacy of a fixed dose RAI regimen in Graves' and toxic nodular hyperthyroid patients. Design and setting Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
4
17
0
Order By: Relevance
“…Lithium treatment resulted in an additional 22.4% increase in cure rate three months post RAI therapy. Our findings are comparable to those from Martin et al, the Pisa group and Zha et al 7,11,18,19 The lower proportions of cure rate observed in our study compared with those from Martin et al and the two studies from the Pisa group can be attributed to the shorter end point of three months in our study compared with at least one year in the others. It is noteworthy that our findings differed from that of Bal et al, who found no difference between the RAI only group and RAI with adjuvant lithium group 20 with cure rates of 68.4% and 68.9% respectively.…”
Section: Cure Ratesupporting
confidence: 88%
See 4 more Smart Citations
“…Lithium treatment resulted in an additional 22.4% increase in cure rate three months post RAI therapy. Our findings are comparable to those from Martin et al, the Pisa group and Zha et al 7,11,18,19 The lower proportions of cure rate observed in our study compared with those from Martin et al and the two studies from the Pisa group can be attributed to the shorter end point of three months in our study compared with at least one year in the others. It is noteworthy that our findings differed from that of Bal et al, who found no difference between the RAI only group and RAI with adjuvant lithium group 20 with cure rates of 68.4% and 68.9% respectively.…”
Section: Cure Ratesupporting
confidence: 88%
“…Our findings were in agreement with those of Martin et al and the Pisa group who both found a significant reduction in time to cure in their studies. 7,18 A later study by the Pisa group also supported our results as they found that 50% of patients who received adjuvant lithium were cured in two months compared with the RAI only group, which had 50% cured in three months. 11 This prompter control of hyperthyroidism is likely due to the fact that release of organic iodine as well as thyroid hormones is blocked by lithium without affecting radioactive iodine uptake (RAIU) by the gland.…”
Section: Time To Curesupporting
confidence: 78%
See 3 more Smart Citations